Perencanaan Struktur Gedung Perkantoran 5 Lantai di Jalan Teuku Umar Kota Semarang (Indonesian Journal of Civil Engineering Study, 2025)
The structural planning for this 5-storey office building is planned to be a building whose structure is earthquake resistant. In building construction planning, it is necessary to obtain effective and efficient structural patterns and dimensions. A building structure located in a vulnerable area must meet standards, be strong and earthquake resistant. Structural Performance Analysis in Multi-Storey Buildings, referring to SNI 1727:2020 – Building Loads, SNI 1726:2019 – Procedures for Earthquake Resistance Planning in Building and Non-Building Structures. Planning for office construction in multi-storey buildings includes the upper and lower structures as well as overall analysis using the Etabs V.20 application. The upper structure includes the roof, beams, columns and floor plates of the building, while the lower structure consists of tie beams. The loads considered in structural element analysis are dead loads, live loads and earthquake loads. The earthquake load entered is the earthquake load using the equivalent static analysis method and response spectrum method. Dimensions of Columns, Beams and Slabs based on Structural Concrete Requirements for Buildings National Standardization Agency (SNI 247: 2019).
Keywords: Structural planning; Earthquake resistant; Response spectrum